A rare cause of acute dysphagia: listeria rhombencephalitis - Hirannya Karunadasa; Robbie Chan; Ronan O'Connor; Alexander Hodge (European Journal of Case Reports in Internal Medicine, 2026)
Introduction: Acute dysphagia is a common presentation to hospital and requires a structured diagnostic approach to distinguish between oropharyngeal and oesophageal causes. Although oesophageal pathology is often suspected, central neurological causes must be considered, particularly in atypical presentations. Listeria monocytogenes is a rare but important cause of central nervous system infection, including rhombencephalitis, which may present with progressive cranial neuropathies and bulbar dysfunction, including acute dysphagia. Early diagnosis is challenging but critical, as delayed recognition is associated with significant morbidity and mortality. Case description: A 37-year-old male presented with acute onset dysphagia and an inability to manage oral secretions following a short prodrome of fever and gastrointestinal symptoms. Initial evaluation suggested oesophageal obstruction; however, urgent endoscopy was unremarkable. His condition deteriorated with aspiration pneumonitis and persistent dysphagia. In the presence of reduced lingual sensation and impaired gag reflex, neuroimaging and lumbar puncture were performed, confirming Listeria rhombencephalitis. Despite targeted antimicrobial therapy, he developed multiple cranial nerve deficits and required a tracheostomy for airway protection. With prolonged intravenous antibiotics and multidisciplinary care, he demonstrated gradual neurological recovery and was discharged for ongoing rehabilitation. Conclusion: This case highlights the importance of a systematic diagnostic framework in acute dysphagia and maintaining a high index of suspicion for alternative causes to avoid diagnostic anchoring. Early recognition of oropharyngeal features and neurological signs should prompt timely neuroimaging and lumbar puncture. Central causes including Listeria rhombencephalitis should be considered early, as prompt targeted therapy is essential to improve outcomes.